(untitled) (EAAE Annual Conference Proceedings, 2023)
To understand the context, from the physical through the sociological to the economic, the architect must conduct field research. For a long time, that primarily meant a tour of the location, but recently, the importance of collecting the opinions of all actors of spatial development is becoming highly recognized. Roughly speaking, these are four groups: the local government members; various expert groups representatives; representatives of companies interested in investment and development; and specific or future potential users. Moderating the conversation of all these groups representatives is a demanding yet rewarding task.